What would Jesus buy? [videorecording (DVD)] - Spurlock, Morgan, 1970-; VanAlkemade, Rob; Talen, William; D., Savitri (Arts Alliance America, 2007)
Bill Talen (aka Reverend Billy) was a lost idealist who hitchhiked to New York City only to find that Times Square was becoming a mall. Spurred on by the loss of his neighborhood and inspired by the sidewalk preachers around him, Bill bought a collar to match his white caterer's jacket, bleached his hair and became the Reverend Billy of the Church of Stop Shopping. Follows Reverend Billy and the Stop Shopping Gospel Choir (a changing group of volunteers) as they go on a cross-country mission to save Christmas from the Shopocalypse.